Biochar-extracted liquor stimulates nitrogen related gene expression on improving nitrogen utilization in rice seedling - Gao, Jian; Ge, Shaohua; Wang, Hailong; Fang, Yunying; Sun, Luming; He, Tianyi; Cheng, Xiaoyi; Wang, Di; Zhou, Xuanwei; Cai, Heqing; Li, Caibin; Liu, Yanxiang; et al. (Frontiers in Plant Science, 2023)
Introduction Biochar has been shown to be an effective soil amendment for promoting plant growth and improving nitrogen (N) utilization. However, the physiological and molecular mechanisms behind such stimulation remain unclear. Methods In this study, we investigated whether biochar-extracted liquor including 21 organic molecules enhance the nitrogen use efficiency (NUE) of rice plants using two N forms (NH4+-N and NO3--N). A hydroponic experiment was conducted, and biochar-extracted liquor (between 1 and 3% by weight) was applied to rice seedlings. Results The results showed that biochar-extracted liquor significantly improved phenotypic and physiological traits of rice seedlings. Biochar-extracted liquor dramatically upregulated the expression of rice N metabolism-related genes such as OsAMT1.1, OsGS1.1, and OsGS2. Rice seedlings preferentially absorbed NH4+-N than NO3--N (p < 0.05), and the uptake of NH4+-N by rice seedlings was significantly increased by 33.60% under the treatment of biochar-extracted liquor. The results from molecular docking showed that OsAMT1.1protein can theoretically interact with 2-Acetyl-5-methylfuran, trans-2,4-Dimethylthiane, S, S-dioxide, 2,2-Diethylacetamide, and 1,2-Dimethylaziridine in the biochar-extracted liquor. These four organic compounds have similar biological function as the OsAMT1.1 protein ligand in driving NH4+-N uptakes by rice plants. Discussion This study highlights the importance of biochar-extracted liquor in promoting plant growth and NUE. The use of low doses of biochar-extracted liquor could be an important way to reduce N input in order to achieve the purpose of reducing fertilizer use and increasing efficiency in agricultural production.